Pleasures of Music - Barzun, Jacques (London Cassell, 1977)
Edited by Jacques Barzun. The sensitive critic, the perceptive listener, the lover of words and music will find this one of the most diverse and diverting collections of writings on music. It is a browsing book for people who approach the arts with wit and insight. More important, it is for the civilized individual who understands and values tradition.
An Anthology edited and with an introduction by Jacques Barzun
Keywords: Music history